Rhetoric of conflict settlement in Yoruba traditional societies (2020)
The modem justice system in Africa is clearly overwhelmed by the number of cases in the courts because of population explosion and inadequate resources to sustain the system. This trend has necessitated a fresh look at the traditional conflict settlement system and its potential to complement and relieve the modem justice system. Even though it has been playing large roles in conflict management at the grassroots communities in settling civil cases and supporting peaceful coexistence among the people, the system has not received adequate official recognition and hence its contributions has been limited. The paper explores the traditional conflict settlement system in Yoruba communities of southwest Nigeria and the procedures and rhetoric that sustains it. The potentials to complement the modem justice system towards achieving a sustainable peaceful society are discussed and suggestions are made on how the inherent benefits of traditional conflict settlement system in Yoruba communities could be maximally exploited if granted official recognition